Retrospective study of the use of an influenza disease two-tiered classification system to characterize clinical severity in US children - Amber Hsiao; Philip O. Buck; Arnold Yee; John Hansen; Edwin M. Lewis; Laurie L. Aukes; Emad Yanni; Rafik Bekkat-Berkani; Anne Schuind; Nicola P. Klein (Taylor & Francis Group, 2020)
In children <5 years, influenza is associated with higher risk of serious disease and hospitalization when compared with other age groups. Influenza vaccination reduces the risk of influenza and vaccination may attenuate the severity of disease. Recent studies in Europe suggest that classifying influenza disease as mild versus moderate-to-severe (M-S) using a novel definition may be clinically significant. We retrospectively evaluated whether this M-S definition also characterized influenza severity in a cohort of US children. We included children <18 years at Kaiser Permanente Northern California with PCR-confirmed influenza during the 2013-2014 influenza season. We classified children as M-S if they had ≥1 symptom: fever >39°C, acute otitis media, lower respiratory tract infection (LRTI), or extra-pulmonary complications; otherwise, they were classified as mild. We used multivariable log-binomial models to assess whether M-S influenza disease was associated with increased healthcare utilization. Nearly half of the 1,105 influenza positive children were classified as M-S. Children 6-35 months had the highest proportion of M-S disease (35.1%), mostly due to LRTI (63.2%) and fever (44.6%). Children ≥6 months who had M-S disease were associated with a 1.6 to 2.8 times increased likelihood of having had an emergency department or any follow-up outpatient visits. Those who had M-S disease were associated with an increased likelihood of receiving antibiotics, with the highest likelihood in children 6-35 months (RR 9.0, 95% CI 4.1, 19.8). While more studies are needed, an influenza classification system may distinguish children with more clinically significant disease.